Pengembangan Multimedia Interaktif Menggunakan Lectora Inspire pada Materi Pengendalian Hayati untuk Mata Kuliah Entomologi: Development of Interactive Multimedia Using Lectora Inspire on Biological Control Materials for Entomology Course - Wella Galih Permata; Asni Johari; Ali Sadikin (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2021)
Lectora Inspire learning media is a website-based learning media innovation that can be used to make presentations. This study aimed to develop interactive multimedia learning media using Lectora Inspire on biological control material for entomology courses to determine student responses and lecturer responses to the resulting multimedia learning media. This research was conducted on biology education students who took entomology elective courses (MKP) classes of 2017 and 2018. The trials were conducted on six (small group) and 14 (large group) students. This type of research is Research and Development (R&D) with the ADDIE model. Data collection instruments were validation sheets for material and media experts, lecturer interviews, and student and lecturer perception questionnaires. The results of the assessment of material experts are 95%, and media experts are 95%. The results of the small group trial were 87.8% in the very feasible category, and the large group was 87.3% very feasible. Based on the data analysis, it can be concluded that Lectora Inspire media on biological control material is suitable for use in learning.